Cytotoxic effect of damnacanthal, nordamnacanthal, zerumbone and betulinic acid isolated from Malaysian plant sources - Mohamed Alitheen, Noorjahan Banu; Abd Rahman, Mashitoh; Yeap, Swee Keong; Mustafa, Shuhaimi; Ali, Abdul Manaf; Lajis, Nordin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The present study was to evaluate the toxicity of damnacanthal, nordamnacanthal, betulinic acid and zerumbone isolated from local medicinal plants towards leukemia cell lines and immune cells by using MTT assay and flow cytometry cell cycle analysis. The results showed that damnacanthal significantly inhibited HL-60 cells, CEM-SS and WEHI-3B with the IC50 value of 4.0 μg/mL, 8.0 μg/mL and 3.3 μg/mL, respectively. Nordamnacanthal and betulinic acid showed stronger inhibition towards CEM-SS and HL-60 cells with the IC50 value of 5.7 μg/mL and 5.0 μg/mL, respectively. In contrast, Zerumbone was demonstrated to be more toxic towards those leukemia cells with the IC50 value less than 10 μg/mL. Damnacanthal, nordamnacanthal and betulinic acid were not toxic towards 3T3 and PBMC compared to doxorubicin which showed toxicity effects towards 3T3 and PBMC with the IC50 value of 3.0 μg/mL and 28.0 μg/mL, respectively. The cell cycle analysis exhibited that damnacanthal exerted its toxicity effect towards HL-60 cells by inducing apoptosis with value of 25% after 72 hours treatment. Thus, these compounds could be the potential anticancer drug with less toxic side effect.